2002
DOI: 10.1159/000064490
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala Substitution in the Peroxisome Proliferator-Activated Receptor-Gamma Is Associated with Increased Leptin Levels in Women with Type-2 Diabetes mellitus

Abstract: Objective: To analyze the relationship between the peroxisome proliferator-activated receptor-γ (PPARγ2) Pro12Ala variant and type-2 diabetes mellitus and its correlation with some cytokine determinants of insulin resistance such as tumor necrosis factor (TNF)-α and leptin. Methods: The PPARγ2 Pro12Ala genetic polymorphism was studied in 167 type-2 diabetic patients and 63 healthy controls. Serum leptin and plasma-soluble TNF-R2 were measured. Results: Women carriers of the Pro12Ala mutation exhibited higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 33 publications
6
20
1
Order By: Relevance
“…Indeed, it was shown, in vivo , that Ala12 allele is associated with a reduced LPL activity in postheparin plasma [93]; higher leptin levels were observed in Pro12Ala compared to Pro12Pro carrier women [92]. The effect of Pro12Ala on increased leptin levels is likely to be supported by a study in women with functional hyperandrogenism (FOH), in which the authors demonstrated that Ala allele was more frequent in FOH women than in healthy controls (36% versus 28%) and that leptin levels were higher in nonobese FOH women compared to controls [100].…”
Section: Pparg Target Genes: Polymorphisms Haplotypes and Gene Ementioning
confidence: 99%
“…Indeed, it was shown, in vivo , that Ala12 allele is associated with a reduced LPL activity in postheparin plasma [93]; higher leptin levels were observed in Pro12Ala compared to Pro12Pro carrier women [92]. The effect of Pro12Ala on increased leptin levels is likely to be supported by a study in women with functional hyperandrogenism (FOH), in which the authors demonstrated that Ala allele was more frequent in FOH women than in healthy controls (36% versus 28%) and that leptin levels were higher in nonobese FOH women compared to controls [100].…”
Section: Pparg Target Genes: Polymorphisms Haplotypes and Gene Ementioning
confidence: 99%
“…Adipose-derived cytokines leptin and adiponectin levels have been shown to increase insulin action [184, 185]. Indeed, Ala12 allele is associated with higher plasma levels of leptin in Spanish diabetic women [186]. In comparison, two Japanese population studies show that Ala12 allele carriers have significantly lower plasma levels of adiponectin than Pro12 allele carriers [187, 188] and another two case-control studies in either diabetic patients or women with PCOS fail to find significant change in serum adiponectin levels [189, 190].…”
Section: Cellular Mechanism Of Pparγ2pro12ala Polymorphismmentioning
confidence: 99%
“…Previous studies demonstrated that the PPARG Pro12Ala variant allele is associated with higher insulin sensitivity, lower body mass index (BMI) (11), decreased risk of T2DM (12)(13)(14), higher high-density cholesterol (HDL) levels (11) and decreased incidence of CVD (15). Additionally, it was demonstrated that the PPARG Pro12Ala polymorphism may alter the plasma levels of leptin, adiponectin, resistin and ghrelin (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%